Efeito in vitro de complexo entre cetoconazol e ácido p-sulfônico calix[6]areno sobre Leishmania amazonensis e Leishmania infantum - Botelho, Bianca de Oliveira (2019)
Ketoconazole has been described as a leishmanicidal agent, however, the low aqueous solubility of the drug may limit its bioavailability and therapeutic efficacy. p-sulphonic acid calix[n]arene has been used to improve solubility and efficacy of drugs. The aim of this work was evaluate the in vitro effect of the ketoconazole/p-sulfonic acid calix[6]arene inclusion complex (CLX/CTZ) on promastigote forms of Leishmania amazonensis and Leishmania infantum, as well as their toxicity to DH82 macrophages. The leishmanicidal effect and toxicity of CLX/CTZ, pure ketoconazole (CTZ) and the physical mixture of the two compounds (PM) were evaluated by the resazurin method. The IC50 value of CLX/CTZ, CTZ and PM on the L. amazonensis promastigotes forms was 3.95, 14.35 and 13.87 µM; and in L. infantum was 6.74, 17.47 and 17.54 µM, respectively. The CLX/CTZ, CTZ and PM showed no toxicity to DH82 cells. CLX/CTZ has demonstrated higher leishmanicidal activity than CTZ and PM. CLX/CTZ also presented low toxicity to macrophages, representing a promising alternative for use in preclinical trials for leishmaniasis treatment.